Glucose 6 Phosphate Dehydrogenase (G6PD) quantitation using biosensors at the point of first contact: a mixed method study in Cambodia - Bipin Adhikari; Rupam Tripura; Lek Dysoley; James J. Callery; Thomas J. Peto; Chhoeun Heng; Thy Vanda; Ou Simvieng; Sarah Cassidy-Seyoum; Benedikt Ley; Kamala Thriemer; Arjen M. Dondorp; et al. (Malaria Journal, 2022)
Abstract Background Quantitative measurement of Glucose-6-Phosphate Dehydrogenase (G6PD) enzyme activity is critical to decide on appropriate treatment and provision of radical cure regimens for vivax malaria. Biosensors are point-of-care semi-quantitative analysers that measure G6PD enzyme activity. The main objective of this study was to evaluate the operational aspects of biosensor deployment in the hands of village malaria workers (VMWs) in Cambodia over a year. Methods Following initial orientation and training at Kravanh Referral Hospital, each VMW (n = 28) and laboratory technician (n = 5) was provided a biosensor (STANDARD SD Biosensor, Republic of Korea) with supplies for routine use. Over the next 12 months VMWs convened every month for refresher training, to collect supplies, and to recalibrate and test their biosensors. A quantitative self-administered questionnaire was used to assess the skills necessary to use the biosensor after the initial training. Subsequently, VMWs were visited at their location of work for field observation and evaluation using an observer-administered questionnaire. All quantitative questionnaire-based data were analysed descriptively. Semi-structured interviews (SSIs) were conducted among all participants to explore their experience and practicalities of using the biosensor in the field. SSIs were transcribed and translated into English and underwent thematic analysis. Results A total of 33 participants completed the training and subsequently used the biosensor in the community. Quantitative assessments demonstrated progressive improvement in skills using the biosensor. VMWs expressed confidence and enthusiasm to use biosensors in their routine work. Providing G6PD testing at the point of first contact avoids a multitude of barriers patients have to overcome when travelling to health centres for G6PD testing and radical cure. Deploying biosensors in routine work of VMWs was also considered an opportunity to expand and strengthen the role of VMWs as health care providers in the community. VMWs reported practical concerns related to the use of biosensor such as difficulty in using two pipettes, difficulty in extracting the code chip from the machine, and the narrow base of buffer tube. Conclusions VMWs considered the biosensor a practical and beneficial tool in their routine work. Providing VMWs with biosensors can be considered when followed by appropriate training and regular supervision. Providing community management of vivax malaria at the point of first contact could be key for elimination.